2005
DOI: 10.1038/sj.bmt.1705107
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-producing CD8+ T cells may be an immunological hallmark of chronic GVHD

Abstract: Summary:Chronic graft-versus-host disease (cGVHD) occurs in approximately 60-80% of those who survive over 100 days after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the pathophysiology of cGVHD is poorly understood. To gain more insight into the immunological mechanism of cGVHD, we examine cytokine production of peripheral blood T cells from 19 patients in the chronic phase of allo-HSCT. The percentage of IFN-c-producing CD8 þ T cells among CD8 þ T cells was significantly higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…Our finding that CD8 + T cells can discriminate the peptide/MHC level encountered during activation and respond by producing IL-4 that tunes their antigen sensitivity is a significant step forward in our understanding of the ability of CD8 + T cells to respond to environmental signals. The observation that CD8 + T cells can produce IL-4 is in agreement with other reports (25,(43)(44)(45); however this is, to our knowledge, the first demonstration of an antigen dependent mechanism through which this function is regulated. The ability of IL-4 to act as a regulator of CD8 + T cell function has been reported in models of exogenously added IL-4 (22-27, 34, 46-52).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that CD8 + T cells can discriminate the peptide/MHC level encountered during activation and respond by producing IL-4 that tunes their antigen sensitivity is a significant step forward in our understanding of the ability of CD8 + T cells to respond to environmental signals. The observation that CD8 + T cells can produce IL-4 is in agreement with other reports (25,(43)(44)(45); however this is, to our knowledge, the first demonstration of an antigen dependent mechanism through which this function is regulated. The ability of IL-4 to act as a regulator of CD8 + T cell function has been reported in models of exogenously added IL-4 (22-27, 34, 46-52).…”
Section: Discussionsupporting
confidence: 92%
“…The question arises as to why CD8 + T cells would possess this autocrine regulatory mechanism. IL-4 producing-CD8 + T cells elicited in vivo have been identified in chronic graft vs. host disease (45). These T cells tend to co-express IFNγ similar to what we observed in our studies.…”
Section: Discussionsupporting
confidence: 89%
“…In breast cancer, an increased level of IL-4 was considered as a part of disease pathomechanism [21], while in stem cell transplantation setting IL-4 producing CD8+ lymphocytes seemed to contribute to development of chronic Graft-versusHost Disease [22]. In our observation, a significant increase in IL-4 in cultures only from recipients suggests the role of this cytokine in the underlying disease of those patients.…”
Section: Discussionsupporting
confidence: 45%
“…We combined treosulfan with fludarabine, thymoglobulin, and cyclophosphamide (60 mg/kg × 2 doses), resulting in a transplant preparative regimen that was lower in intensity than Conv MA regimens but stronger than the previous RIC regimen 9 . Pro‐inflammatory cytokines during HSCT have been associated with adverse outcomes 12‐14 . In animal studies, treosulfan has shown to cause lower levels of inflammatory cytokines compared to busulfan and cyclophosphamide, which may provide an additional advantage in particular in patients with HLH.…”
Section: Discussionmentioning
confidence: 99%